Wear Life Prediction on Unfolding Wheel of Steel Ball Detection by Using Numerical Simulation - PAN Cheng yi; LI Xia; ZHAO Yan Ling; XIANG Jing Zhong; LI Wei (Journal of Harbin University of Science and Technology)
Wear is the main failure form of unfolding wheel of steel ball, and the unfolding effect on steel ball surface will be failure when the wear of unfolding wheel achieves a certain degree. Aiming at the problem of the life prediction of unfolding wheel, the critical failure condition is established according to the structure of unfolding wheel and the unfold theory. Based on the classical Archard wear model and the finite element method, the discrete Archard wear model is proposed and the life prediction model of the unfolding wheel of steel ball is established. Using ANSYS software to simulate the wear of unfolding wheel to obtain the relationship equation of wear depth and wear times. The validity of the life prediction method is validated by example of calculation, it provides a theoretical basis for the series design and practical use of unfolding wheel of steel ball.